Telemedicine to promote mental health conditions in Bangladesh during COVID-19 pandemic - Arafat, M. Yeasin; Roy, Abhijeet (International Journal Of Community Medicine And Public Health, 2021)
The coronavirus disease 2019 (COVID-19) is a disease caused by the outbreak of a new virus, known as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). On 11 March 2020, the World Health Organization (WHO) declared the COVID-19 as a global pandemic.1 The first confirmed cases were recorded in Bangladesh on 08 March 2020 and continued to spread.2 Since then, the new realities of work from home, temporary unemployment, home-schooling of children, and lack of physical contact with other family members, friends, and colleagues are taking time to habitual with it. The aftermath of such an outbreak is not only harming physical health but also mental health.3 Therefore it is necessary to identify mental health contexts of COVID-19 and effective therapies to tackle the situations.4 The COVID‐19 pandemic has made a significant change in the healthcare delivery system worldwide, physicians are offering digital health solutions at record, and putting the telemedicine services (i.e. telehealth) at center stage.5 With telemedicine’s help, the burden of mental health can be reduced conveniently during this pandemic.6 Like other countries, Bangladesh has also started telemedicine health services to help the patient psychologically, though there are several barriers to get advantages of this approach.7 This article aims to provide an overview of the importance and necessity of telemedicine in addressing mental health conditions during the COVID-19 pandemic, particularly in Bangladesh.